Ursolic Acid Inhibits Breast Cancer Metastasis by Suppressing Glycolytic Metabolism via Activating SP1/Caveolin-1 Signaling - Wang, Shengqi; Chang, Xu; Zhang, Juping; Li, Jing; Wang, Neng; Yang, Bowen; Pan, Bo; Zheng, Yifeng; Wang, Xuan; Ou, Hesheng; Wang, Zhiyu (Frontiers in Oncology, 2021)
Breast cancer remains the most common malignancy and the leading causality of cancer-associated mortality among women worldwide. With proven efficacy, Oldenlandia diffusa has been extensively applied in breast cancer treatment in Traditional Chinese Medicine (TCM) for thousands of years. However, the bioactive compounds of Oldenlandia diffusa accounting for its anti-breast cancer activity and the underlying biological mechanisms remain to be uncovered. Herein, bioactivity-guided fractionation suggested ursolic acid as the strongest anti-breast cancer compound in Oldenlandia diffusa. Ursolic acid treatment dramatically suppressed the proliferation and promoted mitochondrial-mediated apoptosis in breast cancer cells while brought little cytotoxicities in nonmalignant mammary epithelial cells in vitro. Meanwhile, ursolic acid dramatically impaired both the glycolytic metabolism and mitochondrial respiration function of breast cancer cells. Further investigations demonstrated that ursolic acid may impair the glycolytic metabolism of breast cancer cells by activating Caveolin-1 (Cav-1) signaling, as Cav-1 knockdown could partially abrogate the suppressive effect of ursolic acid on that. Mechanistically, ursolic acid could activate SP1-mediated CAV1 transcription by promoting SP1 expression as well as its binding with CAV1 promoter region. More meaningfully, ursolic acid administration could dramatically suppress the growth and metastasis of breast cancer in both the zebrafish and mouse xenotransplantation models of breast cancer in vivo without any detectable hepatotoxicity, nephrotoxicity or hematotoxicity. This study not only provides preclinical evidence supporting the application of ursolic acid as a promising candidate drug for breast cancer treatment but also sheds novel light on Cav-1 as a druggable target for glycolytic modulation of breast cancer.